Relationship between diet and plasma long-chain n-3 PUFAs in older people: impact of apolipoprotein E genotype - Samieri, Cécilia (The American Society for Biochemistry and Molecular Biology, 2013)
The main risk factors for Alzheimer's disease, age and the ϵ4 allele of the APOE gene (APOE4), might modify the metabolism of n-3 PUFAs and in turn, their impact on cognition. The aim of this study was to investigate the association between dietary fat and plasma concentrations of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in elderly persons, taking the APOE4 genotype into account. The sample was composed of 1,135 participants from the Three-City study aged 65 years and over, of whom 19% were APOE4 carriers. Mean plasma proportions of EPA [1.01%, standard deviation (SD) 0.60] and DHA (2.41%, SD 0.81) did not differ according to APOE4. In multivariate models, plasma EPA increased with frequency of fish consumption (P < 0.0001), alcohol intake (P = 0.0006), and female gender (P = 0.02), and decreased with intensive consumption of n-6 oils (P = 0.02). The positive association between fish consumption and plasma DHA was highly significant whatever the APOE genotype (P < 0.0001) but stronger in APOE4 noncarriers than in carriers (P = 0.06 for interaction). Plasma DHA increased significantly with age (P = 0.009) in APOE4 noncarriers only. These findings suggest that dietary habits, gender, and APOE4 genotype should be considered when designing interventions to increase n-3 PUFA blood levels in older people.